Robotic and Laparoscopic Reconstructive Surgery in Children and Adults - Ost, Michael C.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Robotic and Laparoscopic Reconstructive Surgery In Children and Adults is a unique volume focusing on the union between adult and pediatric urologic surgical techniques. The breadth of this wonderful convergence is most clearly and consistently demonstrated when minimally invasive reconstructive techniques are utilized. This volume describes in detail the surgical steps of the major adult and pediatric reconstructive laparoscopic and robotic cases. Pediatric urologists, adult urologists, fellows, and urology residents will find this volume to be a comprehensive, yet concise, reference for most all robotic and laparoscopic procedures that may be performed within this vast discipline.
I Principles of Reconstructive Laparoscopy and Robotics in Urology -- II Laparoscopic and Robotic Reconstructive Renal Surgery -- III Laparoscopic and Robotic Reconstructive Renal Pelvis Surgery -- IV Laparoscopic and Robotic Reconstructive Ureteral Surgery -- V Laparascopic and Robotic Reconstructive Bladder Surgery -- VI Laparoscopic and Robotic Orchiopexy in Children -- VII Laparoscopic and Robotic Anastomoses for Radical Prostatectomy.
Keywords: Medicine; Surgery; Endoscopic surgery; Urology; Medicine & Public Health; Urology/Andrology.; Minimally Invasive Surgery; Surgery